Congenital Epulis of Newborn - A Case Report - Anjana Bagewadi (Wolters Kluwer Medknow Publications, 2004)
Congenital epulis or gingival granular cell tumor of the newborn is a rare benign tumor which is commonly seen in female infants in the maxillary anterior region. Here is a short case report of the same and review.